“Collaboration Toward One Collective Goal”: A Mixed-Methods Study of Short-Term Learning Outcomes and Long-Term Impacts Among Students Participating in an Undergraduate Community-Based Participatory Research (CBPR) Course - Yigletu, Seblewongel; Kosinski, Karen C.; Kuah, Alison; Alfaro, Kenia; Holmes, Ashley C.; Tendulkar, Shalini A. (Frontiers in Public Health, 2021)
Background: Research shows positive learning outcomes for students participating in service learning. However, the impacts of undergraduate student participation in Community-Based Participatory Research (CBPR) courses are minimally studied. Methods: We used a triangulation mixed-methods design mixed-methods approach to analyze short- and long-term (1-5 years post-course) data collected from 59 undergraduate students across 5 cohorts of a CBPR course (2014-19). Thematic analysis was used to analyze the qualitative data and descriptive statistics and frequencies were generated to analyze the quantitative data. Results: We developed five key themes based on short-term qualitative data: integration of CBPR and traditional research skills; importance of community engagement in research; identity; accountability; and collaboration. Themes from qualitative course evaluations aligned with these findings. Long-term qualitative data revealed that former students gained research knowledge, research skills, and professional skills and then applied these in other settings. This aligns with quantitative findings, where >79% of respondents reported that course participation “extensively” improved their research skills. Post-course, students still reflected on the importance of community engagement in research and reported a substantially enhanced likelihood of civic engagement. Discussion/Conclusions: Students gained critical knowledge and skills that positively impact their ability to engage in community-based work well after the end of course participation. Some students reported considering research-oriented careers and graduate programs for the first time after course participation. Collaborative learning experiences with community partners and members encouraged students to reflect on research designs that center community voices. We stress here that community partnerships require extensive cultivation, but they can create opportunities to translate findings directly back to communities and provide numerous benefits to undergraduate students. We hope that our findings provide the information needed to consider pilot testing practice-based CBPR courses in a variety of public health training contexts.